Marketing Mix Strategy of Mabarrot AlMustasyfa Clinics in the Era of National Health Insurance - Al Abrori, Ucy Nur Hamida; Arimurti, Zhafira Ramadhani; Wijaya, Andriana Putri; Ernawaty (BPJS Kesehatan, 2024)
The National Health Insurance (JKN) has significantly changed the health service, especially in private clinics. Private clinics are offered the opportunity to participate in implementing the JKN to deliver quality care within a cost-control mechanism of capitation payment. Mabarrot AlMustasyfa Clinic is one of the private clinics in the Gresik regency that has contracted with BPJS to serve JKN participants since April 2024. The clinic accepts the capitation payment system, providing unique challenges to increase the satisfaction of the JKN members. In the capitation payment the clinic will receive a higher monthly capitation payment each month if there are new members enrolled in the clinic. However, the clinic faces financial risks if increasing demands and the clinic budget and revenue are constant. To ensure that the operational clinic is financially healthy, the management must have a marketing strategy to attract new members to enrol in the clinic. This study explains the marketing strategy using a marketing mix which consists of 7 P: products, prices, promotions, locations, people, processes, and physical facilities. This case study demonstrates how well the marketing mix is being conducted. The study results show that the Mabarrot AlMustasyfa Clinic has not succeeded due to several obstacles, namely the lack of health services and inadequate facilities with an inappropriate management system. The clinic must be able to face the challenge of increasing patient satisfaction to survive in the JKN era.